A mathematical investigation of RAO diversity coefficients among the communities according to the species morphometry and species taxonomy - Barroga, Kenneth D. (2009)
Although Rao Diversity Coefficient (Rao DIVC) is sensitive to the differences among species, a gap still remains in investigating how the communities are affected when the dissimilarity among the species are in terms of its morphometry and taxonomy. To address such gap, this study determined the effect of using species taxonomic classification and species morphological traits in the computation of Rao DIVC in assessing diversity of ecological communities. Existing methods for measuring the dissimilarity between species were utilized. For species morphometry, Mahalanobis distance was employed, and as for species taxonomy, the proposed method by Warwick and Clarke (1995) was used. As tools for investigation, the calculated Rao DIVCs, Double Principal Coordinate Analysis and Co-inertia Analysis outputs were compared. Based on the findings, Rao diversity coefficients accounting species morphometry (Rsm) and species morphometry (Rst) yielded different results and interpretation. Rsm clearly showed more the variation among communities but contributed less in the analysis, whereas, Rst showed more clearly clusters between the communities which make the interpretation easier. Thus, if the research is time-bound, the best decision would be to make use of the species taxonomy since it is readily available.